Agile applications of artificial intelligence to apparel industry - Gonçalves, R.; Lopes da Costa, R.; Pereira, L.; Dias, Á.; Vinhas da Silva, R.; Teixeira, N. (International Journal of Agile Systems and Management, 2023)
Artificial intelligence systems are increasing its importance in the field of creating value for companies who seek to gain competitive advantage. This is especially true for the online shopping apparel world, in the case of virtual try-on systems. Following this line of thought the theme consumers acceptance of artificial intelligence virtual try-on systems when shopping online apparel came up as a research problem. In this sense this investigation intendeds to study the acceptance by consumers of the virtual try-on artificial systems when buying apparel online according to specific variables previously defined. To assess this, a quantitative approach was used, based on the structural equations model, the partial least squares technique. This research allowed the creation of a new model based on technology acceptance model by including new variables and revealed that the influence of predictive variables on the dependent variable (ATU) is not the same.